1994
DOI: 10.1007/s002040050047
|View full text |Cite
|
Sign up to set email alerts
|

The ambiguous effect of ascorbic acid on chromate induced proteinuria in rats

Abstract: The influence of ascorbic acid (AA, 5 g/kg body weight) on chromate (Cr, 10 mg/kg) induced proteinuria, which is a sensitive parameter of its nephrotoxicity, was investigated in adult female Wistar rats. The concentrations of Cr and ascorbic acid (AA) were determined in renal tissue. Cr nephrotoxicity is related to its intracellular reduction from Cr(VI) to Cr(III). Proteinuria was completely prevented by enhancement of extracellular reduction of Cr(VI) to Cr(III) followed by rapid renal excretion when Cr and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…It may be important to conduct further studies to evaluate this hypothesis. Though a number of studies have found dose-dependent nephrotoxicity with many drugs (Greggi-Atunes, et al, 2000, Martinez-Salgado, et al, 2007 at least one study has reported a reversal of effect similar to ours (Appenroth, et al, 1994). Our findings could be of immense clinical importance if confirmed by further studies because it would caution against co-administration of gentamicin and B-12 complex parenterally and suggest that careful evaluation of patients on concurrent treatment with both drugs may be crucial, especially at the initial phase of treatment.…”
Section: Discussionsupporting
confidence: 78%
“…It may be important to conduct further studies to evaluate this hypothesis. Though a number of studies have found dose-dependent nephrotoxicity with many drugs (Greggi-Atunes, et al, 2000, Martinez-Salgado, et al, 2007 at least one study has reported a reversal of effect similar to ours (Appenroth, et al, 1994). Our findings could be of immense clinical importance if confirmed by further studies because it would caution against co-administration of gentamicin and B-12 complex parenterally and suggest that careful evaluation of patients on concurrent treatment with both drugs may be crucial, especially at the initial phase of treatment.…”
Section: Discussionsupporting
confidence: 78%
“…157 Subsequent animal studies indicated that large parenteral doses (0.5-5 g/kg) of ascorbic acid prevented renal toxicity only when administered within 1-2 hours following the administration of chromate. 158,159 In these studies, the later administration of ascorbic acid was associated either with no effect or with increased nephrotoxicity. There are no clinical studies to support the use of ascorbic acid after the ingestion of Cr (VI) compounds or to determine the potential complication (e.g., oxaluria) of this therapy.…”
Section: Supportive Carementioning
confidence: 93%
“…3 and 4), it can be presumed that Cr(VI) uptake, membrane damage, and the reactions leading to hepatotoxicity were almost completely finished by the time taurine was administered in the posttreatment group; therefore, taurine was no longer able to exert modulating effect against SOD and CAT enzyme depression. Appenroth et al [62] reported that the interval between Cr(VI) and ascorbic acid treatment was critical, and it depended on this period whether or not there is a beneficial effect of the antioxidant. In a recent publication by Sinha et al [36], treatment of hepatocytes with taurine either prior to or in combination (simultaneously) with sodium arsenite protected cells against oxidative stress; in line with our results, taurine pretreatment seems to be more promising.…”
Section: Discussionmentioning
confidence: 99%